32. RESULTS OF EARLY PRESENTATION PEDIATRIC LATERAL CONDYLAR FRACTURE MANAGED BY CLOSED REDUCTION AND PERCUTANEOUS PINING UNDER IMAGE INTENSIFIER (Vietnam Journal of Community Medicine, 2024)
Background: Lateral condyle fracture is an interarticular fracture common in pediatric fracture. Currently, percutaneous reduction and pining has good results but limitted number of studies with long-term follow-up.Purposes: Evaluate the results with a minimum of two-year follow-up.Methods: Retrospective study of 30 cases of early presentation pediatric lateral condylar fracture managed by closed reduction and percutaneous pinning from January 2015 to December 2016. functional and healing evaluation depends on Hardacre scale.Results: Most common age is from 3 to 7 years old with male: female ratio of 4:1. There are grade I 56.7% and grade II 43.3% of Jakob classification. Results according to Hardacre scale are very good 83.4%, good 13.3%, and bad 3.3%. There is a significant correlation between the degree of displacement according to Jakob’s classification and the degree of recovery according to the Hardacre scale (p=0.02). The clinical carrying angle of the fracture arm smaller than the other side accounts for 66.7%, equal for 33.3%; Xray carrying angle at follow-up of < 5˚ is 13.3%, ≥ 5˚ 86.7%.Conclusion: The method is effective for Jackob I and II fracture. There is a significant correlation between the degree of displacement and the degree of recovery.
Keywords: Early presentation lateral condylar fracture, closed reduction, percutaneous pinning, image intensifier.